Association between weight-adjusted-waist index with hepatic steatosis and liver fibrosis: a nationally representative cross-sectional study from NHANES 2017 to 2020 - Shen, Yun; Wu, Yahui; Fu, Minghan; Zhu, Kai; Wang, Jinsheng (Frontiers in Endocrinology, 2023)
Background: The negative effects of obesity on hepatic steatosis and fibrosis have received considerable attention in recent years. The weight-adjusted-waist index (WWI) reflects weight-independent centripetal obesity. Herein, we provide the first investigation of a link between WWI, hepatic steatosis, and liver fibrosis. Methods: We used data from the National Health and Nutrition Examination Survey 2017-2020 to conduct a cross-sectional study. The linear relationship between WWI, controlled attenuation parameters, and liver stiffness measurements (LSM) was investigated using multivariate linear regression models. The nonlinear relationship was described using fitted smoothed curves and threshold effect analyses. Subgroup analyses were performed based on gender, age, body mass index, diabetes, hypertension, drinking, and smoking. Results: This population-based study included 8,176 people, 46.87% of whom were men and 53.13% of whom were women. Multivariate linear regression analysis revealed a significant positive relationship between WWI and hepatic steatosis [CAP, β=7.60, 95% confidence interval (CI) (4.42, 10.78), P<0.0001]. This positive association was stronger when excessive alcohol intake was present compared to when it was absent (P for interaction = 0.031), and when hypertension was present compared to when it was not (P for interaction = 0.014). The linear relationship between WWI and liver fibrosis was not statistically significant on multiple regression analysis [LSM, β=0.03, 95% CI (-0.26, 0.32), P=0.84]. However, a U-shaped association was seen between WWI and LSM, with a negative correlation when WWI < 10.92 and a positive correlation when WWI > 10.92. Conclusion: We report a strong association between WWI and hepatic steatosis, and suggest that it may potentially be used as a simple anthropometric index to predict hepatic steatosis.